MicroRNA Detection: Current Technology and Research Strategies - Hunt, Eric A; Broyles, David; Head, Trajen; Deo, Sapna K (Annual review of analytical chemistry (Palo Alto, Calif.), 2015)
The relatively new field of microRNA (miR) has experienced rapid growth in methodology associated with its detection and bioanalysis as well as with its role in -omics research, clinical diagnostics, and new therapeutic strategies. The breadth of this area of research and the seemingly exponential increase in number of publications on the subject can present scientists new to the field with a daunting amount of information to evaluate. This review aims to provide a collective overview of miR detection methods by relating conventional, established techniques [such as quantitative reverse transcription polymerase chain reaction (RT-qPCR), microarray, and Northern blotting (NB)] and relatively recent advancements [such as next-generation sequencing (NGS), highly sensitive biosensors, and computational prediction of microRNA/targets] to common miR research strategies. This should guide interested readers toward a more focused study of miR research and the surrounding technology.